Detecção de unidades litológicas na bacia de Una-Utinga por espectroscopia de reflectância e dados do sensor multiespectral Aster - Lima, Lilian Graicy Lima Morais (2011)
This study aimed to characterize the spectral lithologic units found in the basin of Una-Utinga (BA) using spectroscopy reflectance techniques.From the development of spectral libraries and hyperspectral processing of ASTER Satellite image strategies were prepared for detection of the characteristic lithologies of these units.Spectral measurements on rock samples were performed in this basin, with the aid of a portable spectroradiometer model ASD-FieldSpec FR3, which acquires spectra in the spectral range of 350-2500nm.The Digital processing of ASTER image consists of the spectral classification by SAM (Spectral Angle Mapper) method. The spectral curves obtained in laboratory were analyzed with basis on literature and the main features of absorption were identified for each lithological type.The Una Group, divided into Bebedouro and Salitre Formation forms the substrate of the basin.Diagnostic features for limestones, dolomites, silexitos and gossans were identified in Salitre Fm. At Bebedouro Formation, lithofacies identified have diagnostic features of sandstone / mudstone and diamictite. For image classification we used three different spectral libraries (or endmembers): 1) derived from the image by PPI tool and n-dimensional, 2) formed by minerals from Reference libraries like USGS and JPL, and 3) formed by the spectra of field samples obtained at laboratory. The results were positive, as were possible to determine at ASTER image areas with predominance of calcite, dolomite, clay minerals, and iron oxides, which constitute the main mineralogy of the rocks formations of the Bebedouro and Salitre formations.